Assessment of construction object financing solutions - Stungurienė, Stanislava; Urbšienė, Laima (Technological and Economic Development of Economy, 2011)
Theoretical and practical issues related to the applicability of the evaluations of construction project financing having regard to the complexity, timeframe and the limited nature of the resources available have been lately increasingly attracting researchers‘ attention. The assessment of decisions as to the timing and volume of funding of a project is extremely important and relevant for any organisation; therefore, it has been considered necessary to explore different models for possible financing by applying empiric and financial models, as well as theoretical mathematical methods. The objective of the present research exercise was to develop an optimal model for the appropriation of financing of defined scope according to different financing scenarios. For that purpose the researchers used a hypothetical reference heuristic financing appropriation plan for four periods of identical duration in three construction objects. By reference to the linear programming theory an optimal plan was identified by assigning, in individual periods and to each object, different priorities rated in points. The financing appropriation plans are assessed in terms of their impact upon the enterprise value that is computed applying the cash flow discounting method and the tax shield effect theory. Since the selection of the financing source is an important factor for the enterprise value the calculations were performed assessing three possible scenarios of the enterprise financing taking into account the enterprise‘s liquidity: a – an enterprise has accumulated sufficient own funds to finance the project, b – an enterprise has accumulated funds sufficient only to pay the interest for borrowed capital, c – an enterprise does not possess any disposable monetary resources to finance the project during its implementation, therefore it capitalizes the interest payable to the bank. It was concluded that under scenario a the selection of a financing plan does not affect the enterprise value, as the enterprise finances the investment from own resources. In the case of scenario b the loan obtained from the purpose of the investment creates additional value, the choice of the plan, however, does not affect the enterprise value. When capitalising the interest payable to the bank under scenario c, the highest value of an enterprise is created in the case of selection of an optimal plan that is developed by setting an overall limit of the amount to be funded, i.e., by prioritizing mathematical logics without referring to the up-front appropriation of financial resources by objects. The present article deals with the theory of the evaluation of investment project solutions. The results of the evaluation of the solutions for construction project financing appropriation are presented by criteria for optimal solutions and possible financing scenarios. Article in English. Statybos objektų finansavimo sprendimų įvertinimas Santrauka. Statybos projektų finansavimo vertinimo teorinių ir praktinių pritaikymo klausimų nagrinėjimas, atsižvelgiant į šių projektų įgyvendinimo sudėtingumą, laiką bei reikalingų išteklių ribotumą, pastaruoju metu sulaukia vis didesnio dėmesio. Sprendimų, kiek ir kada finansuoti projektą, vertinimas yra labai svarbus kiekvienai organizacijai, todėl turi būti tiriami įvairūs galimo finansavimo modeliai, taikant empirinius ir finansų bei matematikos teorijos metodus. Tyrimo tikslas – parengti optimalų statybos projekto nurodytos finansavimo apimties paskirstymo modelį pagal skirtingus finansavimo scenarijus. Tyrimui naudotas sąlygiškas euristinis finansavimo paskirstymo planas keturiems vienodos trukmės laikotarpiams pagal tris objektus. Taikant tiesinio programavimo teoriją, optimalus planas randamas kiekvienam objektui konkrečiu periodu suteikus skirtingus balais įvertintus prioritetus. Finansavimo paskirstymo planai vertinami pagal jų įtaką įmonės vertei, kuri skaičiuojama taikant pinigų srautų diskontavimo ir skolinto kapitalo dėl mokesčių sutaupymo papildomai sukuriamos vertės teoriją. Kadangi įmonės vertei svarbus finansavimo šaltinio pasirinkimas, skaičiuota vertinant tris įmonės finansavimo scenarijus atsižvelgiant į įmonės likvidumą: a – įmonė turi sukaupusi pakankamai nuosavų lėšų projektui finansuoti; b – įmonei pakanka nuosavų lėšų tik palūkanoms už skolintas lėšas sumokėti; c – įmonė neturi laisvų piniginių išteklių projekto įgyvendinimo laikotarpiu, todėl kapitalizuoja bankui mokėtinas palūkanas. Nustatyta, kad a scenarijaus atveju įmonės vertei finansavimo plano pasirinkimas įtakos nedaro, nes ji investicijas finansuoja nuosavomis lėšomis. Pagal b scenarijų investicijai paimta paskola sukuria papildomą vertę, tačiau plano pasirinkimas įmonės vertės neveikia. Kapitalizuojant bankui mokėtinas palūkanas pagal c scenarijų, didžiausia įmonės vertė sukuriama pasirinkus optimalų planą, kuris sudaromas nurodžius bendrą finansuojamos sumos apribojimą, t. y. suteikiant prioritetą matematinei logikai atsisakius išankstinio finansinių išteklių paskirstymo pagal objektus. Straipsnyje nagrinėjama investicinių projektinių sprendimų vertinimo teorija. Statybos objektų finansavimo paskirstymo vertinimo rezultatai pateikti pagal optimalumo kriterijus ir galimus finansavimo scenarijus. Reikšminiai žodžiai: optimalus modeliavimas, statybos projekto vertinimas, įmonės vertė, investavimo sprendimai, finansavimo alternatyvos. First published online 18 Jan 2012